Effectiveness of maintenance therapy of lithium vs other mood stabilizers in monotherapy and in combinations: a systematic review of evidence from observational studies - Kessing, L; Bauer, M; Nolen, W; Severus, E; Goodwin, G; Geddes, J (John Wiley & Sons Ltd, 2018)
Objectives: For the first time to present a systematic review of observational studies on the efficiency of lithium monotherapy in comparison with other maintenance mood stabilizers and in combination. Methods: As part of the International Society for Bipolar Disorders (ISBD) Task Force on Lithium Treatment we undertook a systematic literature search of non-randomized controlled observational studies on 1) lithium monotherapy versus treatment with another maintenance mood stabilizer in monotherapy 2) lithium in combination with other mood stabilizers versus monotherapy. Results: In eight out of nine identified studies including more than a total of 14.000 patients, maintenance lithium monotherapy was associated with improved outcome compared with another mood stabilizer in monotherapy including valproate, lamotrigine, olanzapine, quetiapine, unspecified anticonvulsants, carbamazepine/lamotrigine, unspecified atypical antipsychotics and unspecified antipsychotics. Among the four identified studies including a total of more than 4.000 patients comparing maintenance combination therapy with maintenance monotherapy, a few combination therapies were found to be superior to monotherapy in some analyses, but many were not. Conclusions: The results show the superiority in real life of lithium monotherapy compared with monotherapy with other maintenance mood stabilizers. The four largest register-based studies largely addressed confounding, but, as ever, residual confounding cannot be excluded. Nevertheless, the observational findings substantially add to the findings from randomized controlled trials, whose designs often limit the validity of comparison between medicines.